Investigating the Effectiveness of Using GIPI AI Speaking Assistant to Boost Students’ Speaking Skills. The Case of Second-Year LMD Students of English at the University of Souk-Ahras - Aouaitia Maram (My University, 2024)
Abstract This study investigates the effectiveness of GIPI Assistant, an AI-powered tool, in improving speaking skills of EFL learners. The research aims to examine the impact of GIPI on students’ vocabulary enrichment, pronunciation improvement, and anxiety reduction. it contributes to understanding the role of AI in enhancing speaking skills among EFL learners, potentially influencing the adoption of AI tools like GIPI within educational contexts. True experimental research is designed involving two groups consisting of 28 students of second-year EFL students at the University of Mohamed Cherif Messaadia in Souk-Ahras during the academic year 2023-2024. It assesses the impact of GIPI on students’ speaking skills. This study employs a mixed-methods approach, combining quantitative and qualitative methods for comprehensive insights. Data collection tools include a survey, observations, and post-test to address research questions and hypothesis. The dissertation consists of five chapters covering the problem statement, previous studies, research methodology, data presentation and interpretation, and recommendations. The findings indicate that GIPI application has a substantial immediate effect on enhancing learners’ speaking abilities. ethical considerations ensure participant rights are protected. --------------------- الملخص تسعى هذه الدراسة إلى التحقق من فعالية أداة جيبي المدعومة بالذكاء الاصطناعي في تحسين مهارات التحدث لدى دارسي اللغة الإنجليزية. كما تهدف إلى دراسة تأثير هذه الأداة في إثراء رصيد الطلاب المفرداتي، وتحسين نطقهم، والحد من توترهم أثناء التحدث. تعتمد هذه الدراسة على منهجية البحث التجريبي الحقيقي، حيث تضم مجموعتين، تتألف كل واحدة منهما من 28 طالباً من السنة الثانية لقسم اللغة الإنجليزية بجامعة محمد شريف مساعدية في سوق أهراس، خلال العام الدراسي 2023-2024، لتقييم أثر جيبي على مهارات التحدث لديهم. تستند منهجية البحث إلى أساليب مختلطة، تجمع بين الأساليب البحث الكمي والنوعي، لتوفير رؤى شاملة حول الموضوع. وتشمل أدوات جمع البيانات استبياناً، ومراقبة دورية، واختباراً بعدياً، في محاولة للإجابة على أسئلة البحث والفرضيات المقترحة. تتألف الأطروحة من خمسة فصول، تغطي استعراضاً شاملاً للمشكلة والدراسات السابقة، ومنهجية البحث، وعرضاً للبيانات وتفسيرها، والتوصيات. تشير النتائج إلى أن تطبيق جيبي له تأثير إيجابي كبير وفوري في تعزيز قدرات التحدث لدى المتعلمين. وبشكل عام، يهدف هذا البحث إلى المساهمة في فهم دور الذكاء الاصطناعي في تعلم اللغات، وتقديم رؤى حول تعزيز مهارات التحدث بين دارسي اللغة الإنجليزية، مما قد يؤثر بشكل إيجابي على اعتماد أدوات الذكاء الاصطناعي مثل جيبي في السياقات التعليمية. ------------------ Résumé Cette étude approfondie explore l’efficacité de l’Assistant GIPI, un outil alimenté par l’IA, dans l’amélioration des compétences orales des apprenants en anglais langue étrangère (EFL). Elle vise spécifiquement à évaluer l’impact de GIPI sur trois aspects clés : le vocabulaire, la prononciation et la réduction de l’anxiété chez les étudiants. En utilisant une approche de recherche expérimentale véritable, l’étude compare deux groupes d’étudiants de deuxième année en EFL à l’Université de Mohamed Cherif Messaadia à Souk-Ahras pendant l’année académique 2023-2024.Pour obtenir une compréhension approfondie, cette recherche combine des méthodes quantitatives et qualitatives. Les outils de collecte de données comprennent une enquête préliminaire, des observations en classe et un post-test évaluant les compétences orales des étudiants après avoir utilisé l’Assistant GIPI. Les résultats sont analysés pour répondre aux questions de recherche et tester les hypothèses énoncées. La dissertation est organisée en cinq chapitres pour fournir une structure claire : elle commence par l’énoncé du problème, explore ensuite les études antérieures pertinentes, décrit la méthodologie de recherche utilisée, présente et interprète les données collectées, puis propose des recommandations basées sur les résultats obtenus. Enfin, des considérations éthiques sont intégrées à toutes les étapes de la recherche pour garantir le respect des droits des participants et le traitement équitable des données recueillies. Ces mesures visent à assurer l’intégrité et la validité de l’étude tout en protégeant le bien-être des participants.